Antecedents of Innovative Work Behavior Preparing New City Airport Development - Sri Handari; Alni Rahmawati; Maulidyah Amalia Rizqi; Habib Zhafran Makarim (International Journal of Science and Environment (IJSE), 2025)
This article examines the antecedents of Innovative Work Behavior (IWB) by placing transformational leadership and organizational culture as predictors, and employee engagement as a mediating variable. Research was conducted on Goverment Leader on Yogyakarta Indonesia who have prepare Internasional City Airport Developmet. The selection of the sample was motivated by the urgency of organizational change and work attitudes that must be possessed by office holders related to the development of the Airport City in Indonesia. Researchers distributed questionnaires to Goverment Leader in Airport City Kulonprogo Indonesia. With the 103 respondent of the research, the results of the study show that the innovative behavior of employees is influenced by the built organizational culture and employee engagement. In other words, organizational culture is a predictor of employee engagement and innovative work behavior. However, unlike previous research, this research does not prove that transformational leadership can influence innovative work behavior. The results of this study illustrate the importance of strengthening positive attitudes and innovative behavior of employees through the development of an organizational culture that encourages the creation of ideas and the implementation of ideas for organizational performance that is facing demands for change.